AN ENHANCE CORRUPTION ERADICATION THROUGH A POLITICAL LEGAL APPROACH - Ismaidar Ismaidar; Sukardi Sukardi (Sean Institute, 2023)
The word corruption comes from Latin, namely corruptio or corruptus, which means